2004
DOI: 10.3846/16486897.2004.9636834
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Soil Pollution With Heavy Metals in Lithuanian Military Grounds

Abstract: Military grounds are the largest military activity territories in Lithuania. In some of them, military activities are going on for more than 100 years. Specific nature of long‐term activities carried out in military grounds with military equipment, weapons, ammunition and different busters have caused the anomalies of pollution with heavy metals in some places. And what is more, in many places the environment is polluted with oil products, remains of bullets and explosive devices can be found in tactical field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 2 publications
(1 reference statement)
0
11
0
Order By: Relevance
“…Soil of most regions of the country is less weathered and contains higher contents of most chemical elements than soil of Ašmena-Medininkai Heights (Kadūnas et al 1999). Research was done also on military grounds (Vasarevičius, Greičiūtė 2004;Idzelis et al 2006), landfills (Jaskelevičius, Lynikienė 2009) or near highways (Butkus, Šalčiūnienė 2011 Stream sediments are not only influenced by surface run-off, but also by groundwater discharge (Lachmar et al 2006). Volcanoes (Ernst 2012;Ayris, Delmelle 2012;Calvo et al 2013) and forest fires (Pereira, Ubeda 2010) are the main natural sources of air pollution.…”
Section: Introductionmentioning
confidence: 99%
“…Soil of most regions of the country is less weathered and contains higher contents of most chemical elements than soil of Ašmena-Medininkai Heights (Kadūnas et al 1999). Research was done also on military grounds (Vasarevičius, Greičiūtė 2004;Idzelis et al 2006), landfills (Jaskelevičius, Lynikienė 2009) or near highways (Butkus, Šalčiūnienė 2011 Stream sediments are not only influenced by surface run-off, but also by groundwater discharge (Lachmar et al 2006). Volcanoes (Ernst 2012;Ayris, Delmelle 2012;Calvo et al 2013) and forest fires (Pereira, Ubeda 2010) are the main natural sources of air pollution.…”
Section: Introductionmentioning
confidence: 99%
“…Though an allowed level is not exceeded, it is seen that even medium concentrations are quite big in comparison with a natural environment. A maximum concentration of oil products was established at soil sampling point M3 (.igs 7,8). Such a concentration exceeds three times a maximum allowed concentration.…”
Section: Analysis Of Investigation Resultsmentioning
confidence: 92%
“…The results of investigation revealed that oil product concentrations in the soil of the abandoned military settlement varied from 14,3 to 184,5 mg/kg (.igs 7,8). A medium determined concentration of oil products was equal to 35,3 mg/kg, i e by 29 % less than a maximum allowed concentration defined in the Lithuanian Hygiene Norms (MAC for oil products of 50 mg/kg).…”
Section: Analysis Of Investigation Resultsmentioning
confidence: 93%
“…The motorfield was in the northern part of the territory and covered 76 ha. There were roads and overhead roads, other smaller equipment for improving driving skills [10,13]. Also, in Kairiai Military Ground there was a tank directrix, which covered 319 ha of area -a 4 km route between Klaipėda Channel and the villages of Vaškiai and Lūžgaliai.…”
Section: Introductionmentioning
confidence: 99%
“…The territory of Kairiai Military Ground had a dence net of communication. In the central part of the Military Ground, in a particularly protected airshed, there was a missile which had a particular destination [13,14]. All these activities had a great impact on the environment.…”
Section: Introductionmentioning
confidence: 99%